2022
DOI: 10.1002/acm2.13574
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in linac primary barrier transmission values

Abstract: Primary barrier design for linac shielding depends very sensitively on tenth value layer (TVL) data. Inaccuracies can lead to large discrepancies between measured and calculated values of the barrier transmission. Values of the TVL for concrete quoted in several widely used standard references are substantially different than those calculated more recently. The older standard TVL data predict significantly lower radiation levels outside primary barriers than the more recently calculated values under some circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This was first considered by McDermott et al for an Elekta linac. 3 The density of the concrete is known (2.29 g/cm 3 ), the thickness of the barrier was verified by measurement, and the MU rate of the linac was measured. The only materials unaccounted for in the barrier are rebar, dry wall, and an aluminum laser mounting plate.…”
Section: Barrier Transmission and Tvlmentioning
confidence: 99%
See 4 more Smart Citations
“…This was first considered by McDermott et al for an Elekta linac. 3 The density of the concrete is known (2.29 g/cm 3 ), the thickness of the barrier was verified by measurement, and the MU rate of the linac was measured. The only materials unaccounted for in the barrier are rebar, dry wall, and an aluminum laser mounting plate.…”
Section: Barrier Transmission and Tvlmentioning
confidence: 99%
“…151 (NCRP151), the Institute of Physics and Engineering in Medicine Report 75 (IPEM75), and the International Atomic Energy Agency Report 47 (IAEA47). 3 , 4 , 5 , 6 The concrete TVL data for 4–18 MV are identical in NCRP151 and IPEM75. Measurements have shown that the TVL data from these publications sometimes underpredicts air kerma rates by up to a factor of 3.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations